Quadruplex Nucleic Acids - Chaires, Jonathan B.; Graves, David (Topics in Current Chemistry,, 2013)
Gaining Insights into the Small Molecule Targeting of the G-Quadruplex in the c-MYC Promoter Using NMR and an Allele-Specific Transcriptional Assay, by Christine E. Kaiser, Vijay Gokhale, Danzhou Yang and Laurence H. Hurley.- Higher-Order Quadruplex Structures, by Luigi Petraccone.- Investigation of Quadruplex Structure Under Physiological Conditions Using In-Cell NMR, by Robert Hänsel, Silvie Foldynová-Trantírková, Volker Dötsch and Lukás Trantírek.- Circular Dichroism of Quadruplex Structures, by Antonio Randazzo, Gian Piero Spada and Mateus Webba da Silva.- Molecular Crowding and Hydration Regulating of G-Quadruplex Formation, by Daisuke Miyoshi, Takeshi Fujimoto and Naoki Sugimoto.- Visualizing the Quadruplex: From Fluorescent Ligands to Light-Up Probes, by Eric Largy, Anton Granzhan, Florian Hamon, Daniela Verga and Marie-Paule Teulade-Fichou.- Calculation of Hydrodynamic Properties for G-Quadruplex Nucleic Acid Structures from in silico Bead Models, by Huy T. Le, Robert Buscaglia, William L. Dean, Jonathan B. Chaires and John O. Trent.- Energetics of Ligand Binding to G-Quadruplexes, Concetta Giancola and Bruno Pagano.- Tetramolecular Quadruplex Stability and Assembly, by Phong Lan Thao Tran, Anne De Cian, Julien Gros, Rui Moriyama and Jean-Louis Mergny.